Volumetric Growth of Cervical Schwannoma as a Predictor of Surgical Intervention. (January 2017) - Alemi, A. Sean; Heaton, Chase M.; Ryan, William R.; El-Sayed, Ivan; Wang, Steven J.
Objective: Cervical schwannomas are benign tumors that commonly present as asymptomatic masses and are managed with observation, radiation, or surgery. To our knowledge, the rate of volumetric change seen on serial imaging is not currently used to determine surgical candidacy. We assess average growth rates and determine whether growth rate of cervical schwannoma predicts having undergone surgery. Study Design: Case series with chart review. Setting: Quaternary academic medical center. Subjects and Methods: Patients were identified with at least 2 imaging studies and pathologic or imaging characteristics of cervical schwannoma. Volume was calculated with the formula 4/3π xyz, with x, y, and z representing the 3 orthogonal dimensions. Volume and rate of volume change were compared among observed, surgical, and gamma knife groups. Results: Thirteen patients were identified and divided into subgroups: surgical (n = 5), observation (n = 6), and gamma knife (n = 2). Mean follow-up time was 21 months (range, 1-80 months) and not significantly different among subgroups. The average changes in volume were 3.61 cm 3 /mo (entire group), –2.75 cm 3 /mo (observation), 11.97 cm 3 /mo (surgery), and 1.78 cm 3 /mo (gamma knife). Average initial volume for the entire group was 124.4 cm 3 (range, 5-608 cm 3 ) and 142 cm 3 (range 5-613) at follow-up. The surgical group had a statistically significant change in volume ( P = .03). A statistically significant difference in growth rate was seen between the surgical and observation groups ( P = .016) and between the surgical group and all nonsurgical patients ( P = .011). Conclusions: Rate of tumor growth can be used in the evaluation of patients with cervical schwannoma, and it may predict surgical intervention.